Effects of different feeding rate on growth and condition factor of Chitala lopis - Boby Muslimin; Mirna Dwirastina; Yulianto Triwibowo; Siti Rachmi Indahsari; Arif Wibowo; Kurniawan Kurniawan; Rendy Ginanjar; Mochammad Zamroni; Vitas Atmadi Prakoso; Dewi Apriyanti (Depik, 2023)
Chitala lopis, also known as giant featherback, is a fully protected fish species on Indonesian official list due to the susceptibility to exploitation. Several studies showed that the conservation of aquatic resources, such as giant featherback, could be achieved through the implementation of fish farming practices and optimization of feed use. Therefore, this study aimed to determine effect of different feeding rate on growth pattern, performance, and condition factor of the first generation of giant featherback. The first generation of fish was collected from the natural reproduction of broodstock in the earthen ponds. A total of 5 samples were then randomly divided into three treatment groups and reared in the nine net cages installed in the earthen pond. The stocking density in each group was three fish per cage, and the treatments were carried out in triplicates. Feed given comprised fish bycatch as control (T0) (5% of the total weight) and freshwater shrimp, Caridina sp. with two different feeding rates, namely 5% (T1) and 7% (T2) of the total weight. The mean initial weight of all the samples in this study was 41 3.85 g. The results showed that the highest survival and absolute growth rates (29.96.38 g, 78 11%) were obtained in T1, but were not significantly different (p0.05). Furthermore, the highest average relative growth rate was also found in T1 (76.2818.61%) and significantly different compared to other treatments (p0.05). Growth pattern of fish at the beginning of the experiment was negative allometric (0.54), showing a low correlation (0.03), but became positive allometric (4.17) at the end, with moderate correlation (0.66). The results also showed that the highest condition factor was obtained in T2 (0.780.03), and there was a significant effect (p0.05). Based on the results, Caridina sp. had a positive and significant impact on the weight growth of the first generation of giant featherback compared to other studies.Keywords:CultivationFeeding rateGiant featherbackCaridina sp.Rasbora sp.